Sunset song [book club bag] - Gibbon, Lewis Grassic, 1901-1935 (Canongate, 2015)
When Jean Guthrie, broken by repeated childbirth, dies along with her baby twins, her daughter Chris is left to run the rented family farm, along with her elder brother Will and their domineering father. Faced with a choice between doing her duty, and the seductive but distant world of books and learning, Chris eventually decides to remain in her rural community, bound by her intense love of the land. However, Will's departure for Australia, and her father's death, change everything. Her marriage to farmer Ewan Tavendale brings a measure of happiness - but clouds of war are gathering on the horizon...